LATAR BELAKANG TENGKORAK PATOLOGIS DARI PARUH PERTAMA ABAD KE-20 M: DISKUSI BIOANTROPOLOGI HISTORIS DAN BIOARKEOLOGIS - Suriyanto, Rusyad Adi; Indriati, Etty; Koesbardiati, Toetik; Murti, Delta Bayu (Berkala Arkeologi, 2012)
The environment affects someone’s life, since the environment in the womb to the environment in which he was born and lives first. A-biotic, biotic and socio-cultural environment always have a role in modifying their physic and culture. Role in the care and nurture the baby in the form of the socialization, internalization, and growth-development bring health consequences in the following period. This research aimed to identify a pathological skull from the first half of the 20th century, and discuss the results in a historical bioanthropology and bioarchaeological perspective. The researchers observed and examined the pathological evidences, and determined the diagnosis. Furthermore, the researchers discussed the results with reference to the historical and socio-cultural data associated with the atmosphere and events in the life of the individual. The researchers have given broad perspective in viewing human beings as biological and cultural beings.